First Ground‐Based Conjugate Observations of Stable Auroral Red (SAR) Arcs. Issue 6 (20th June 2019) - Martinis, C.; Baumgardner, J.; Mendillo, M.; Taylor, M.J.; Moffat‐Griffin, T.; Wroten, J.; Sullivan, C.; Macinnis, R.; Alford, B.; Nishimura, Y.
Abstract: During the geomagnetic storm of 1 June 2013, all‐sky imagers located at geomagnetically conjugate locations at Millstone Hill, USA (42.6°N, 71.4°W, 50.9° mag lat) and at Rothera, Antarctica (67.5°S, 68.1°W, ‐53.2° mag lat), allowed us to measure a stable auroral red (SAR) arc simultaneously in both hemispheres for the first time. The arc measured in one hemisphere was observed very close to its conjugate location in the opposite hemisphere. While spatial characteristics, such as equatorward motion and latitudinal extent, were similar at both sites, morphological properties, for example, arc brightness and shape of the poleward edges, differed. The overall brightness of the northern hemisphere arc was considerably weaker, by a factor of 2‐3, throughout the night. Reduced magnetospheric forcing, in a short time interval between 0345 UT and 0445 UT, led to decreased SAR arc brightness and reduced equatorward motion at both sites. A substorm occurring near 0500UT provided additional energization that increased the SAR arc brightness as well as the speed of the equatorward motion. These results provide evidence of a complex coupling between energy sources in the inner magnetosphere and the ionospheric receptor conditions within the subauroral domain at opposite ends of the same geomagnetic field line. Key Points: First simultaneous observations of magnetically conjugate SAR arcs show a brighter arc in the Southern Hemisphere Seasonal variations in SAR arc brightness are caused by different local background ionospheric conditions Similar changes in brightness and motion of SAR arcs occur in both hemispheres and are related to changes in magnetospheric forcing